Understanding pathogen population structure and virulence variation for efficient resistance breeding to control cucurbit powdery mildews. (19th April 2021) - Lebeda, Aleš; Sedláková, Božena; Křístková, Eva; Widrlechner, Mark P.; Kosman, Evsey
Abstract: Cucurbit powdery mildew (CPM) is caused most frequently by well‐differentiated obligate erysiphaceous ectoparasites Golovinomyces orontii and Podosphaera xanthii, which vary in their ecology and virulence. All economically important cucurbit crops host both of these CPM species. Breeding of cucurbits for CPM resistance is highly important worldwide, but adequate knowledge of CPM species determination, as well as virulence structure, population dynamics, and spatiotemporal variation of these pathogens, has not yet been achieved. New tools have been developed to enhance research on CPM virulence variation for more efficient breeding and seed and crop production. A set of differential genotypes of Cucumis melo, with high differentiation capacity, may contribute substantially to understanding of variation in CPM virulence at both individual and population levels. Long‐term observations (2001–2012) of CPM pathogens in the Czech Republic were used to analyse virulence variation within and among annual CPM populations and demonstrate the utility of recently developed tools for studying species variability and virulence variation of CPM pathogens worldwide. Detailed analyses of diversity and spatiotemporal fluctuations in the composition of CPM populations provide crucial information for shaping breeding programmes and predicting the most effective sources of race‐specific resistance. The primary aim of this work was to create a uniform framework for determination of CPM species structure and diversity, virulence phenotypes, virulence and phenotype frequencies, phenotype complexity, dynamics, and variation within and among CPM populations. In addition, practical advice is presented on how to select the most relevant data and interpret them for use in cucurbit resistance breeding. Abstract : A framework for data determination and interpretation on powdery mildews was developed including species structure; virulence phenotypes, frequency and complexity; spatiotemporal variation; and their use in resistance breeding. ​